Anteseden dari Consumers’ Csr Engagement on Social Media pada Restoran Cepat Saji - Rasyifa Shaliha; Robert Kristaung; Fatik Rahayu (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research was conducted to examine the influence of CSR associations and motivation based on need for social bonding on consumers' CSR engagement on social media. This research had 200 respondents who filled out a questionnaire distributed via social media. This research uses the Structural Equation Modeling (SEM) data analysis method. The results of the research conducted are: (1) There is a positive influence of CSR associations on motivation based on need for social bonding, (2) There is a positive influence of motivation based on need for social bonding on consumers' CSR engagement on social media.